Respostas
respondido por:
1
(a + b)³ = (a + b) (a + b) (a + b) = a³ + 3a²b + 3ab² + b³
-3ab (a + b) = -3a²b - 3ab²
Por fim, juntando, temos: a³ + 3a²b + 3ab² + b³ + (-3a²b - 3ab²)
O 3a²b e o -3ab² cancelam e o 3ab² e o -3ab² também.
Logo, a resposta é: a³ + b³.
-3ab (a + b) = -3a²b - 3ab²
Por fim, juntando, temos: a³ + 3a²b + 3ab² + b³ + (-3a²b - 3ab²)
O 3a²b e o -3ab² cancelam e o 3ab² e o -3ab² também.
Logo, a resposta é: a³ + b³.
weslet:
nao intendi
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás